The coupled WO3-AgBr nanocatalyst, part II: Synthesis, characterization, and the boosted photocatalytic activity towards metronidazole in an aqueous solution - Elaheh Shabanian-Broujeni; Alireza Nezamzadeh-Ejhieh (Heliyon, 2024)
The AgBr and WO3 nanoparticles (NPs) were synthesized and coupled, and the coupled AgBr-WO3 binary catalyst, as well as the individual AgBr and WO3 NPs, were then characterized by XRD, FTIR, DRS, and SEM-EDX. XRD results showed the formation of orthorhombic WO3 cubic AgBr crystals. The crystallite sizes of 45, 28, and 45 nm were estimated by the Scherrer formula for the as-prepared AgBr, WO3, and AgBr-WO3 catalysts, respectively. The DRS study estimated band gap energies using both absorption edge wavelengths and the Kubelka-Munk model. The band gap energies of 2.72, 3.06, and 2.92 eV were obtained for the direct electronic transitions of AgBr, WO3, and AgBr-WO3. The ECB (potential position) of AgBr and WO3 were estimated to be 0.01 and 0.52 V, while their EVB values were 2.60 and 3.55 V, respectively. Typical FTIR absorption bands of W‒OH, the W‒O‒W, and AgBr bonds have appeared at 1637 cm−1, 823 (and 766) cm−1, and 1384 cm−1, respectively. The pHpzc of 4 was estimated for the individual and coupled catalysts. In studying the photocatalytic activity of the catalysts in the photodegradation of metronidazole (MNZ) a boosted activity was achieved for the coupled system. This increased activity depends on the maximum AgBr:WO3 mole ratio in a 1:3 mol ratio. Grinding time applied to prepare the coupled catalyst has also varied the photocatalytic activity.